Investigation of Solid Energy Potential of Wood and Bark Obtained from Four Clones of a 2-Year Old Goat Willow - Shin, Soo-Jeong; han, sim-hee (Frontiers in Energy Research, 2014)
To investigate the solid raw material characteristics of willow (Salix caprea) bark and woody core, this study analyzed overall chemical composition, monosaccharide composition, ash content, and main ash composition of both tree components. Significant differences were observed between the two in terms of chemical composition, carbohydrate composition, ash content, and major inorganics. The ash content in bark was 3.8–4.7%, compared with 0.6–1.1% in the woody core. Polysaccharide content in the woody core was 62.8–70.6% but was as low as 44.1–47.6% in the bark. The main hemicelluloses consisting of monosaccharides were xylose in the case of the woody core, and xylose, galactose, and arabinose in the case of bark. Woody core biomass of willow provides superior solid fuel raw material, as compared with bark biomass, with higher heating values, less ash content, and less slagging-causing material.